Pengembangan Bahan Ajar Pendidikan Agama Islam pada Lembaga Pendidikan Islam dalam Era Digital - Arman Paramansyah; Didi Wahyudi; Duduh Mamduh; Haris Abdul Aziz; Arjun Said; Rina Maenatul Munawaroh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted to find out digital-based Islamic Religious Education Learning of Islamic learning educational institutions in the digital era. The approach in this writing uses a qualitative approach. Data was collected through the library research method. The process of assessing Islamic religious education in this digital era makes it more effective and efficient by paying attention to Islamic teaching